Kebijakan Ketenagakerjaan Internasional Dan Peran Atase Ketenagakerjaan Dalam Perlindungan Pekerja Migran - Dwihastini, Evi Rosa; Perkasa, Didin Hikmah; Saluy , Ahmad Badawi (Syntax Literate, 2025)
International labor policies play a crucial role in ensuring the protection of migrant workers’ rights. Globalization and increasing labor mobility across countries necessitate effective regulations and comprehensive policies to protect migrant workers from exploitation and legal uncertainties. This article examines international labor policies implemented by various countries and international organizations such as the International Labour Organization (ILO) and the strategic role of labor attachés in enforcing protection for migrant workers. The research employs a policy analysis method with a descriptive-qualitative approach based on literature reviews and secondary data. The findings indicate that international labor policies still face challenges in regulatory harmonization between countries, compliance with labor standards, and the effectiveness of law enforcement mechanisms. The role of labor attachés as government representatives in providing protection, advocacy, and legal assistance for migrant workers is a key factor in ensuring optimal policy implementation. This study concludes that coordination between labor-sending and receiving countries, strengthening the capacity of labor attachés, and enhancing international cooperation are essential to establishing a more effective and sustainable protection system for migrant workers.